Correlation between methotrexate pharmacokinetic parameters, and clinical and biological status in rheumatoid arthritis patients (1995)
To determine the correlation between the pharmacokinetic (PK) parameters of methotrexate (MTX), clinical status and laboratory test results in rheumatoid arthritis (RA) patients.22 patients (4 M/18F, mean age: 50 +/- 12 years, mean duration of RA: 8.5 +/- 6.5 years, mean duration on MTX: 8 +/- 10 months) were included in a prospective study. The mean dose of MTX administered was 6 +/- 0.7 mg/m2 of body area/week. No patient received any nonsteroidal antiinflammatory drug (NSAID). Blood and urine samples were collected over 24 hours (9 blood samples). The MTX concentrations were assayed by fluorescence polarization immunoassay. Clinical parameters (Ritchie articular index, morning stiffness, joint pain count, joint swelling count), hematological, liver and renal function tests, and ESR were recorded. Correlations between the patients' PK parameters, laboratory tests and clinical status were carried out using Pearson's correlation coefficient test.A significant correlation was observed between the Ritchie articular index, morning stiffness and the area under the curve (p = 0.009 and p = 0.026, respectively). No correlation was found with the other parameters.These results suggest that when the patient's disease activity is higher, the AUC becomes more important, reflecting a greater body exposure to MTX.